MOTIVASI PENGUNJUNG BERWISATA KE OBJEK WISATA PANTAI PADANG KOTA PADANG - Rangkuty, Jeka Yolando (journal of residu, 2019)
This research was motivated by the number of visits in 2016 which increased dramatically from the previous year, while some problems were found in Padang Beach Tourism Objects, such as the amount of garbage on the beach, the presence of illegal parking, the number of wild street singers, but this was not an obstacle for visitors for traveling. This study aims to determine the Motivation of Visiting Visitors to Padang Beach Tourism Objects in Padang City, which are reviewed from 2 indicators, namely Internal Factors and External Factors. This type of research is quantitative descriptive survey method. The population of this study is domestic visitors who travel to Padang Beach attractions. The data collection technique is done by using a questionnaire (questionnaire) with a Likert scale that has been tested for validity and reliability. Then the data analysis through descriptive analysis to obtain an overview of the frequency distribution of data that includes the maximum and minimum values, Mean, Median, standard deviation and level of achievement of respondents. With presentations and levels of respondents' achievement on each indicator. The results showed that the motivation of visitors to travel to Padang Beach attractions as a whole was in a very good category with an average value of 42.7333. while based on indicators, (1) Internal factors are in a very good category with an average value of 27.6333. (2) Internal factors are in a very good category with an average value of 15.1000.